2006
DOI: 10.1186/1471-2296-7-49
|View full text |Cite
|
Sign up to set email alerts
|

Literacy and health outcomes: a cross-sectional study in 1002 adults with diabetes

Abstract: Background: Inconsistent findings reported in the literature contribute to the lack of complete understanding of the association of literacy with health outcomes. We evaluated the association between literacy, physiologic control and diabetes complications among adults with diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
95
4
16

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 125 publications
(121 citation statements)
references
References 31 publications
6
95
4
16
Order By: Relevance
“…In our study, only 30% of the patients reached this target, which is alarming. On the other hand, we did not find any relationship between literacy level and glycemic control, which is supported by other studies [12,19,20] while Jahanlou, et al [13] and Fisher [21] observed a moderate inverse relationship. The difference could be due to inclusion of illiterate patients in our study, while theirs was delimited to low literate and literate patients.…”
Section: Discussionsupporting
confidence: 81%
“…In our study, only 30% of the patients reached this target, which is alarming. On the other hand, we did not find any relationship between literacy level and glycemic control, which is supported by other studies [12,19,20] while Jahanlou, et al [13] and Fisher [21] observed a moderate inverse relationship. The difference could be due to inclusion of illiterate patients in our study, while theirs was delimited to low literate and literate patients.…”
Section: Discussionsupporting
confidence: 81%
“…Although a previous study indicated that patients with limited functional HL experienced poor clinical outcomes such as higher A1C level (18), other studies did not support this association (12)(13)(14)19,20). Some researchers found higher rates of diabetes complications in patients with limited functional HL (12,18), but another study reported that the significant differences disappeared after adjusting for confounders (19).Inconsistent findings on the relationship between HL and diabetes care and outcome suggest that optimal selfmanagement of diabetes may not depend solely on a patient's ability to read health information (19). Greater value may be This study sought to examine the psychometric properties of three newly developed scales for measuring functional, communicative, and critical HL among patients with type 2 diabetes in order to propose a measure of HL that overcomes the limitations of previous studies.…”
mentioning
confidence: 40%
“…However, the diabetes self-efficacy score was not significantly different among those with different functional HL levels; instead, the self-efficacy score was associated with self-management behaviors (17). Although a previous study indicated that patients with limited functional HL experienced poor clinical outcomes such as higher A1C level (18), other studies did not support this association (12)(13)(14)19,20). Some researchers found higher rates of diabetes complications in patients with limited functional HL (12,18), but another study reported that the significant differences disappeared after adjusting for confounders (19).…”
Section: Diabetes Care 31:874-879 2008mentioning
confidence: 56%
See 2 more Smart Citations